Characterization of the Three-Variate Inverted Dirichlet Distributions - Ben Farah, Mohamed (Armenian Journal of Mathematics, 2023)
In this paper, we prove a characterization of three-variate inverted Dirichlet distributions by an independence property. The main technical challenge was a problem involving the solution of a related functional equation.